2012
DOI: 10.1186/1756-0500-5-548
|View full text |Cite
|
Sign up to set email alerts
|

Design and process evaluation of an informative website tailored to breast cancer survivors’ and intimate partners’ post-treatment care needs

Abstract: BackgroundOn-line provision of information during the transition phase after treatment carries great promise in meeting shortcomings in post-treatment care for breast cancer survivors and their partners. The objectives of this study are to describe the development and process evaluation of a tailored informative website and to assess which characteristics of survivors and partners, participating in the feasibility study, are related to visiting the website.MethodsThe development process included quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(84 citation statements)
references
References 38 publications
0
84
0
Order By: Relevance
“…BREATH and STRIDE also specifically targeted particular outcomes (i.e., distress and physical activity). The Oncowijzer and Prostate Cancer Education and Resources for Couples ( PERC ) studies focused on cancer survivors and their partners during the transition into survivorship (see Table for trial details).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…BREATH and STRIDE also specifically targeted particular outcomes (i.e., distress and physical activity). The Oncowijzer and Prostate Cancer Education and Resources for Couples ( PERC ) studies focused on cancer survivors and their partners during the transition into survivorship (see Table for trial details).…”
Section: Resultsmentioning
confidence: 99%
“…Higher attrition in the online intervention arms may have been due to participants struggling with the Web‐based nature of the trial (Au; Ps) . Some authors suggested that accessing the intervention added burden and/or required routine adjustments (Au; Ps) . However, some studies reported lower levels of attrition than average for online trials for cancer survivors (Q; Au) , .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations